Quantifying distortions from pollution in a R&D endogenous growth model - Sequeira, T. N.; Ferreira-Lopes, A. (Estudios de Economía, 2014)
In this note we study the distortions in an endogenous growth model developed by Grimaud and Tournemaine (2007), where new pieces of knowledge are produced in a R&D sector and used to reduce pollution emissions. Using this model along with a realistic calibration, we conclude that the economy strongly underinvests in R&D, such that the policy maker would need to implement a strong tax-subsidy scheme to correct it. We suggest that a subsidy to human capital can also decrease the gap between market and optimal allocations.